2011
DOI: 10.1200/jop.2010.000096
|View full text |Cite
|
Sign up to set email alerts
|

Role of Axillary Staging in Women Diagnosed With Ductal Carcinoma In Situ With Microinvasion

Abstract: Background: Axillary staging via sentinel node biopsy (SLNB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Authors reporting a high incidence of positive sentinel lymph nodes argue in favor of sentinel lymph node biopsy in all patients with microinvasive carcinoma, 9,19,28,30,31 whereas authors reporting the low incidence of positive sentinel lymph nodes have questioned whether sentinel lymph node biopsy should be performed in all such patients. 32,[34][35][36][37][38] The wide variation in reported incidence can be explained in part by the diversity in the histopathologic definition of microinvasive carcinoma used in various reports. In 1982, Lagios et al, 40 Later, the 5th edition of the AJCC staging manual defined microinvasive carcinoma as extension of carcinoma cells beyond basement membrane with no single focus 41 mm, whereas Silver and Tavassoli 11 defined it as a single focus of invasive carcinoma p2 mm or up to three foci of invasion, each p1 mm in greatest dimension.…”
Section: Discussionmentioning
confidence: 95%
“…Authors reporting a high incidence of positive sentinel lymph nodes argue in favor of sentinel lymph node biopsy in all patients with microinvasive carcinoma, 9,19,28,30,31 whereas authors reporting the low incidence of positive sentinel lymph nodes have questioned whether sentinel lymph node biopsy should be performed in all such patients. 32,[34][35][36][37][38] The wide variation in reported incidence can be explained in part by the diversity in the histopathologic definition of microinvasive carcinoma used in various reports. In 1982, Lagios et al, 40 Later, the 5th edition of the AJCC staging manual defined microinvasive carcinoma as extension of carcinoma cells beyond basement membrane with no single focus 41 mm, whereas Silver and Tavassoli 11 defined it as a single focus of invasive carcinoma p2 mm or up to three foci of invasion, each p1 mm in greatest dimension.…”
Section: Discussionmentioning
confidence: 95%
“…When comparing treatments of patients with DCISM in different national cancer centers, the data showed that there were less breast conserved surgery (BCS) performed in patients in Chinese cancer center than those in US patient large-volume centers (1.1% VS 47.8e68%) [20,26,27]. In addition, no significant difference of the overall survival rate between patients with DCIS and DCISM was observed after median 100 months follow-up (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…According to this, DCIS comprises a spectrum from low-grade DCIS to high-grade disease with microinvasion (Badruddoja, 2012;Lee et al, 2012). Although DCIS is considered non-invasive, invasive components sometimes are detected in the lesion, recognized as DCIS with microinvasion when the invasive component is less than 1 millimeters in its largest diameter (Pimiento et al, 2011); these are unusual in lesions smaller than 2.5 cm (Siziopikou, 2013) and constitute 10-20% of all cases (Zhang et al, 2012). Transformation of in situ ductal lesions to invasive forms occurs more frequently and sooner in high grade and comedo lesions, local invasive recurrence is also more common in these (Estevez et al, 2010;Sorum et al, 2010;Patani et al, 2011).…”
Section: 2771 Change Of Ductal Carcinoma In Situ Of the Breast Over mentioning
confidence: 99%
“…The necessity of SND in cases of DCIS harboring microinvasion is controversial. Pimiento et al (2011) reviewed 87 cases of DCIS with microinvasion in their institution and found no risk factor for lymphatic invasion such as palpable mass, higher grades or comedonecrosis. Nevertheless, these researchers propose the use of SND in all cases of microinvasion accompanying DCIS (Pimiento et al, 2011).…”
Section: 2771 Change Of Ductal Carcinoma In Situ Of the Breast Over mentioning
confidence: 99%
See 1 more Smart Citation